Understanding Terror : Perspectives for Canadians. - Kassam, Karim-Aly S. (Calgary : University of Calgary Press, 2010)
Understanding Terror takes a historical approach to consideration of terror through specific examples and its presence in the media in North American society and particularly in Canada. Contributors to the volume include journalists, scholars, and public policy experts, many of whom have dealt with the impact of terror or experienced it first-hand. Their aim is to examine specific events, reflect on how those events might be interpreted, and provide historical context, all the while encouraging the reader to question preconceived characterizations of this highly charged political and cultural issue. --Publisher's description.
Introduction: Why Try to Understand Terror?; Terror & Its Boundaries; How Canada Confronts Terrorism: Canadian Responses to 9/11 in Historical & Comparative Context; Accounting for Disaster: The Quest for "Closure" After Aerial Mass Murder -- The Downing of Air India Flight in Comparative Perspective; The Word "Terrorism" & Its Impact on Public Consciousness; Groping in the Dark: How the Media, Absent a Frame of Reference, Fumbled the Danish Cartoon Controversy; The Terrorist "Other": The Fundamentalist & the Islamist; Maintaining Environmental Priorities in the Age of Terrorism; Responding to the Terror of Genocide: Learning from the Rwandan Genocide of 1994; Psycho-dynamics of Terror: A Perspective on the Evolution of Western Civilization; Conclusion: "The Global War on Terror" Overdetermined as a Clash of Civilizations.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Terrorism; Terrorism -- Canada; Terrorism; Terrorisme; Terrorisme -- Canada; terrorism; POLITICAL SCIENCE / Terrorism; Terrorism; Canada; Electronic books